1987
DOI: 10.1038/325631a0
|View full text |Cite
|
Sign up to set email alerts
|

A novel c-abl protein product in Philadelphia-positive acute lymphoblastic leukaemia

Abstract: Activation of cellular proto-oncogenes as a result of chromosomal abnormalities has been implicated in the development of some human malignancies. Perhaps one of the most striking examples of this association occurs in chronic myelogenous leukaemia, where the Philadelphia (Ph) translocation results in substitution of the 5' end of the c-abl proto-oncogene with bcr gene sequences. A unique hybrid bcr-abl message is produced. As the Ph translocation is also present in some patients with acute lymphoblastic leuka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(88 citation statements)
references
References 28 publications
1
86
0
1
Order By: Relevance
“…The resulting BcrAbl proteins are termed P185 BCR-ABL or P210 BCR-ABL. Unlike the normal Abl protein, both BcrAbl proteins possess an activated tyrosine protein kinase activity (Konopka et al, 1984;Kloetzer et al, 1985;Kurzrock et al, 1987).…”
mentioning
confidence: 99%
“…The resulting BcrAbl proteins are termed P185 BCR-ABL or P210 BCR-ABL. Unlike the normal Abl protein, both BcrAbl proteins possess an activated tyrosine protein kinase activity (Konopka et al, 1984;Kloetzer et al, 1985;Kurzrock et al, 1987).…”
mentioning
confidence: 99%
“…20,21 In P210 BCR-ABL this N-terminal variable region is replaced by the N-terminal 902 amino acids of BCR ( Figure 1). A related fusion protein, P190 BCR-ABL , contains the N-terminal 426 amino acids of BCR and is found in Philadelphia chromosome positive (Ph + ) acute lymphocytic leukemia (ALL) [3][4][5] (Figure 1). The product of both BCR-ABL chimeric…”
Section: Domain Structure Of the Chimeric Bcr-abl Oncoproteinmentioning
confidence: 99%
“…1,2 The product of BCR-ABL gene is usually a chimeric BCR-ABL protein of either 210 kDa or 190 kDa associated, respectively, with CML and acute lymphocytic leukemia (ALL). [2][3][4][5] A much rarer third species of 230 kDa that may be preferentially associated with a milder form of CML has recently been identified. [6][7][8][9] The CML stem cell generates a dominant multilineage clone which overproduces all hematopoietic progenitors (colony-forming cells, CFCs) as well as more differentiated granulocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Imatinib is a moderately potent inhibitor of the kinase BCRABLp210, the fusion protein product of a chromosomal translocation, named Philadelphia chromosome (Ph), which is involved in the pathogenesis of chronic myeloid leukaemia (CML) (Druker et al, 2001a;Mauro and Druker, 2001;O'Dwyer and Druker, 2001;Chabner and Roberts, 2005) and of the BCR-ABLp190 product, which is mainly associated with B-cell acute lymphoblastic leukaemia (B-ALL) (Chan et al, 1987;Clark et al, 1987;Hermans et al, 1987;Kurzrock et al, 1987;Melo, 1996). It has been shown that when imatinib is used to treat patients with chronic-phase CML, 90% seem to achieve complete haematological remission and many lose cytogenetic evidence of the malignant clone (Druker et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%